SMART SURVEILLANCE: A REVIEW OF RECENT ADVANCEMENTS, APPLICATIONS, AND ETHICAL CONSIDERATIONS - Ammad Hussain, Muhammad Azam, Muhammad Zia-ul-Rehman, Misbah Altaf, Nighat Siddiqui, Laiba Khan (Spectrum of Engineering Sciences, 2025)
Smart surveillance systems are rapidly evolving due to advancements in artificial intelligence (AI), the Internet of Things (IoT), and edge computing. This review examines the recent progress in smart surveillance technologies, focusing on their applications in various domains, including public safety, smart cities, and healthcare. The review also addresses the ethical considerations and challenges associated with the deployment of these systems, such as privacy concerns and algorithmic bias. Furthermore, it identifies future research directions and opportunities for innovation in the field.